Al-Jawahiri’s poetic image in critical discourse - Ayoob Ali Othman; Jalil Hassan Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Al-Jawahri is an outstanding poet and is considered the successor of Al-Mutanabbi. His poetry aroused the interest of critics and researchers, and the poetic image occupies a high position in his poetry. Critics and researchers paid attention to it, and found that the poet had complete knowledge of the importance of the poetic image, which is a major element of his poetic art, and his genius is evident in it. This image varies greatly. According to the poet’s personality and his emotional and psychological state. Since Al-Jawahri is fond of heritage, he derived most of his poetic images from the ancient Arab heritage and reuses them in his own way.